Frequency of renal artery stenosis and associated factors in patients undergoing coronary angiography - Fardin Mirbolouk; Arsalan Salari; Asieh Ashouri; Marjan Mahdavi-Roshan; Mahboobe Gholipour (Society of Diabetic Nephropathy Prevention, 2019)
Background: Coronary artery disease (CAD) is the first cause of mortality in developed and developing countries, including Iran. Identifying high-risk patients can save many from morbidity and mortality. Renal artery stenosis (RAS) seems to be equivalent to CAD in patients with cardiovascular risk. Objectives: The present study aimed to determine the prevalence, severity, and extent of RAS and its predictors in patients with confirmed CAD on coronary angiography. Patients and Methods: All patients suspected of ischemic heart disease (IHD), who underwent diagnostic coronary angiography at Heshmat heart hospital, Iran were recruited (May 2015 to June 2016). Patients with confirmed CAD underwent non-selective renal angiography, which was categorized as mild, moderate or severe based on luminal diameter narrowing more than normal >0% to 50%, between 50%-70% and more than 70%, respectively. Results: Of 233 patients, RAS was observed in 123 (53%). Around 20% were mild, 10% were moderate and 23% were severe. Additionally, RAS in 37% was unilateral and in 16% were bilateral. Besides,19%, 25% and 56% of patients had atherosclerosis in one, two and three vessels, respectively. There was no correlation between the CAD severity and severity of RAS (P=0.807). Conclusions: Higher prevalence of RAS in patients with hyperlipidemia (60% vs. 40%) was detected. Its association with variables affecting CAD indicates that RAS can be a predictor of CAD. Therefore, simultaneous assessment of RAS in coronary angiography can be a good screening method for CAD beside earlier diagnosis of kidney disease.